ANALISIS PELAKSANAAN PERKAWINAN BEDA AGAMA DI INDONESIA - Elia Juan Markus; Rr Ani Wijayati; Pandiangan, L Elly AM (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Every human being must establish a relationship between men and women which then leads to the level of marriage. In carrying out a marriage, it must be based on the provisions of laws and regulations, but in the development of the times, marriages occur between men and women of different religions. Interfaith marriage itself is a relationship between a man and a woman who want to form a family (household) by adhering to different religions and beliefs. Marriages of various religions can be found in various areas, both urban and rural. Based on Article 2 paragraph (1) and paragraph (2) Law Number 1 of 1974 concerning Marriage states that (1) "Marriage is legal, if it is carried out according to the laws of each religion and belief." (2) Each marriage is recorded according to the applicable laws and regulations, so that it can be said that marriages can be carried out in accordance with their respective religions and beliefs and to obtain validation of interfaith marriages must go through a court judge's decision.